2017
DOI: 10.1002/wat2.1206
|View full text |Cite
|
Sign up to set email alerts
|

From curiosity to commodity: a review of the evolution of sachet drinking water in West Africa

Abstract: The private sector continues to play an important role in filling local drinking water supply gaps across the Global South. In West Africa, a perfect storm of rapid population growth, infrastructure mismanagement, and globalization of consumer markets has resulted in the advent of an entire new industry around packaged water, primarily ‘sachet water’ sold in mechanically sealed plastic sleeves. Most local governments and international development agencies have historically perceived sachet water as a passing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 110 publications
0
55
0
Order By: Relevance
“…This classification scheme does not fully address newer water services, such as tanker or packaged/bottled water, which are becoming important sources despite highly variable quality and reliability in some places (e.g. Stoler 2017). Better measurement precision is needed to assess the dynamic reliability of water sources in cross-cultural contexts.…”
Section: Established Methods For Assessing Household Water Insecuritymentioning
confidence: 99%
“…This classification scheme does not fully address newer water services, such as tanker or packaged/bottled water, which are becoming important sources despite highly variable quality and reliability in some places (e.g. Stoler 2017). Better measurement precision is needed to assess the dynamic reliability of water sources in cross-cultural contexts.…”
Section: Established Methods For Assessing Household Water Insecuritymentioning
confidence: 99%
“…Explaining what then drives consumption of PDW, if not income, has led to an even more detailed focus on the individual consumer to explain PDW supply. Stoler documents a growing evidence base of micro-consumer studies for West Africa, where an increased specification of who is consuming explains what are identified as "choices" in drinking water as a "budding evidence base regarding microeconomic consumer trends that have helped us better understand who drinks sachet water, where, and what individual level factors shape their choices" [12] (p. 4).…”
Section: Situating Explanations Of Pdw Supplymentioning
confidence: 99%
“…Stoler highlights variations in quality for sachet water in Accra [13]; Sharma and Bhaduri flag that contamination events are under-reported in Delhi [10]; and online media documents contamination events are still occurring in Indonesian cities [35]. However, over the years, as general conclusions seem to be that quality of PDW is improving through self-regulation of the domestic industry (for Indonesia, see World Bank, 2015 [4]; for West Africa, see Stoler (2017) [12], public health research has highlighted the significance of PDW as form of supply in contexts where it is of superior quality to other "improved" sources. A recent systematic review of global research on PDW water safety concluded PDW products are substantially less likely to be contaminated than alternative water sources for consumption, including piped water [36].…”
Section: Situating Explanations Of Pdw Supplymentioning
confidence: 99%
See 2 more Smart Citations